Comparison of clavicular hook plate with and without coracoclavicular suture fixation for acute acromioclavicular joint dislocation - Hao-Ming Chang; Chih-Kai Hong; Wei-Ren Su; Tzu-Hao Wang; Chih-Wei Chang; Ta-Wei Tai (Acta Orthopaedica et Traumatologica Turcica, 2019)
Objective: The aim of this study was to compare the clinical and radiographic outcomes of clavicular hook plate fixation with and without coracoclavicular (CC) tape augmentation for the treatment of acute unstable AC dislocation. Methods: We treated 47 patients (31 men and 16 women; mean age: 47 years (range, 21–81)) with unstable acute AC dislocations (Rockwood III–V) and divided them into two groups according to the treatment modality, with hook plate fixation (hook plate group) or hook plate plus CC tape augmentation (combined group). We assessed radiologic findings, such as subacromial osteolysis and AC osteoarthritis. We also evaluated the clinical outcomes using a visual analogue scale (VAS) for pain, as well as the University of California at Los Angeles (UCLA) Shoulder Rating Scale and the American Shoulder and Elbow Surgeons (ASES) Shoulder Score. Results: We found that the combined group had less subacromial osteolysis upon radiography, although the CC distance was similar in both groups (119 ± 29.7% of contralateral side CC distance in hook plate group versus 119 ± 34.8% in the combined group, p = 0.77). Compared with the hook plate group, the combined group had a lower VAS score (4.5 ± 2.3 in hook plate group versus 2.3 ± 1.4 in the combined group, p < 0.001), better UCLA scores (19.9 ± 4.9 in hook plate group versus 27.2 ± 4.0 in the combined group, p < 0.001) as well as better ASES scores (51.9 ± 17.8 in hook plate group versus 73.8 ± 13.1 in the combined group, p < 0.001) at 3 and 6 months after surgery. Conclusion: Hook plate fixation plus CC tape augmentation may prevent subacromial osteolysis and yield better short-term functional outcomes. Level of Evidence: Level III, Therapeutic Study. Keywords: Acromioclavicular joint, Acromioclavicular dislocation, Hook plate, Coracoclavicular augmentation, Shoulder